Evaluation of the influence of fluoroquinolone chemical structure on stability: forced degradation and in silico studies - André Valle de Bairros; Danillo Baptista Pereira; Everson Willian Fialho Cordeiro; Clésio Soldateli Paim; Fabiana Ernestina Barcellos da Silva; Marcelo Donadel Malesuik; Fávero Reisdorfer Paula (Universidade de São Paulo, 2018)
ABSTRACT Fluoroquinolones are a known antibacterial class commonly used around the world. These compounds present relative stability and they may show some adverse effects according their distinct chemical structures. The chemical hydrolysis of five fluoroquinolones was studied using alkaline and photolytic degradation aiming to observe the differences in molecular reactivity. DFT/B3LYP-6.31G* was used to assist with understanding the chemical structure degradation. Gemifloxacin underwent degradation in alkaline medium. Gemifloxacin and danofloxacin showed more degradation perceptual indices in comparison with ciprofloxacin, enrofloxacin and norfloxacin in photolytic conditions. Some structural features were observed which may influence degradation, such as the presence of five member rings attached to the quinolone ring and the electrostatic positive charges, showed in maps of potential electrostatic charges. These measurements may be used in the design of effective and more stable fluoroquinolones as well as the investigation of degradation products from stress stability assays.